Christian Oxyrhynchus: texts, documents, and sources - Blumell, Lincoln H.; Wayment, Thomas (Baylor University Press, 2015)
"Authoritative, comprehensive presentation of Christian texts and texts about Christians in the Oxyrhynchus papyri"--